Feed Markets in the Late Dry Season across Agro-Ecological Zones in Burkina Faso - Ayantunde, Augustine A.; Doamba, E.; Hebie, M.; Sogoba, D.; Same, R.; Blummel, Michael (International Livestock Research Institute, 2021)
Limited access to adequate quantities of high-quality feed is a major constraint to livestock productivity in smallholder systems in the West African Sahel. As a result of the increase in the livestock population and the associated growth in the demand for feeds, feed markets have sprung up in many cities and towns in the region. However, there is little available information on price variations for different feed types across agro-ecological zones in Burkina Faso. Information on feed price and quality is essential to developing strategies to match feed supply with demand. Surveys on the price and quality of feeds at nine feed markets in peri-urban areas across the four agro-ecological zones in Burkina Faso were conducted in the late dry season (March–May) in 2019. In each location, at least 10 feed sellers were interviewed. Samples of major feeds on sale at the markets were collected for laboratory analysis. Cowpea hay had the highest price of 394±53 FCFA per kg DM in Ouagadougou while the feed with the lowest price was sorghum straw, which was 30±2 FCFA per kg DM in Ouahigouya. For nearly all feeds, the prices were highest in Ouagadougou, which is presumably a reflection of higher demand. There was no correlation between price and quality (nitrogen concentration and in vitro organic matter digestibility (IVOMD) in the Ouagadougou market. However, there was a significant (P<0.05) positive relationship between price and nitrogen concentration in Dori, and between price and IVOMD in Bobo-Dioulasso and Ouahigouya markets. The results suggest that increasing demand for feed tends to drive up price particularly in the urban areas regardless of the quality. The findings in Dori, Bobo-Dioulasso and Ouahigouya indicate that there is opportunity to develop feed pricing based on quality.